2011
DOI: 10.1016/j.jcrs.2011.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cataract surgery and postoperative visual outcome in rural central India

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
2
12
3
1
Order By: Relevance
“…A higher prevalence was also associated with female gender in first generation and with presence of hypertension in second generation immigrants. This is consistent with evidence from a previous study in rural India which reported associations of female gender and arterial hypertension along with age and diabetes with higher cataract surgery rate [18]. In contrast, except higher levels of education (polytechnic and university) in first generation immigrants, none of the socioeconomic variables had any influence on the prevalence of cataract surgery among both the generations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A higher prevalence was also associated with female gender in first generation and with presence of hypertension in second generation immigrants. This is consistent with evidence from a previous study in rural India which reported associations of female gender and arterial hypertension along with age and diabetes with higher cataract surgery rate [18]. In contrast, except higher levels of education (polytechnic and university) in first generation immigrants, none of the socioeconomic variables had any influence on the prevalence of cataract surgery among both the generations.…”
Section: Discussionsupporting
confidence: 91%
“…The magnitude of under-corrected refractive error in our study was higher than that reported in CIEMS (41.8%) [18] but lower than that reported in SiMES (60%) [22]. In our study, 10.9% of all the pseudophakic eyes had post-operative VI.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The prevalence of pseudophakia in our cohort is similar to that reported in other regions of the world: e.g., the Singapore Malay Eye Study (4.7%) [4], the Beaver Dam Eye Study in Wisconsin (3.1%) [16], the Australian Blue Mountains Eye Study (6.0%) [17], the Barbados Eye Study (3.0%) [18] and the Central India Eye and Medical Study (5.0%) [7]; however, other Indian studies of urban regions have reported figures as high as 9.4% [9,19]. In China, the prevalence of pseudophakia is lower, as reported in the Beijing Eye Study 2006 [20] and 2009 [5] and the China Nine-Province Survey [10].…”
Section: Discussionsupporting
confidence: 83%
“…Our results are lower than those of Nangia et al [10] in 2011 in India, which reported that 64% had received unilateral surgery.…”
Section: Clinical Features Antecedentscontrasting
confidence: 91%